Hypercoagulable state as demonstrated by thromboelastometry in hemoglobin E/beta-thalassemia patients: Association with clinical severity and splenectomy status - Natesirinilkul R. (2017)
© 2016 Elsevier Ltd. All rights reserved. Introduction Patients with hemoglobin E/beta-thalassemia disease (E/β) are at risk of thromboembolism. Rotational thromboelastometry (ROTEM®) can be used to determine a hypercoagulable state. The objective was to describe the hemostatic and thromboelastometric changes in pediatric patients with E/β with different clinical severity, in comparison with healthy children as controls. Materials and methods Fifty-three pediatric patients with E/β and 21 healthy children were enrolled. The clinical severity of E/β was categorized by using the clinical severity scores. All subjects were tested for complete blood count, protein C activity (PC), total protein S (PS), antithrombin (AT), D-dimer and fibrinogen (Fib) levels and thromboelastometry, measured by ROTEM®. Results The levels of PC (65.7 vs 118.5%), PS (46.8 vs 78.4%), AT (95.7 vs 105.7%) and Fib (217 vs 294 mg/dL) were significantly lower, and the platelet count (PLT) was significantly higher in the patient group than the controls. The maximum clot firmness (MCF) of patients with moderate disease who were previously splenectomized (seven patients) and patients with severe disease (nine patients) were higher than patients who had intact spleen with moderate disease, patients with mild disease and controls (P < 0.05). Only PLT had significant correlation with MCF (P < 0.05). Conclusions Hypercoagulable state was demonstrated by ROTEM® in patients with E/β with severe disease and who were previously splenectomized. The hypercoagulable state was associated with the higher numbers of PLT rather than the decrease of PC, PS, and AT.